Transfer‐Enabled Fabrication of Graphene Wrinkle Arrays for Epitaxial Growth of AlN Films. Issue 1 (13th October 2021) - Song, Yuqing; Gao, Yaqi; Liu, Xiaoting; Ma, Jing; Chen, Buhang; Xie, Qin; Gao, Xin; Zheng, Liming; Zhang, Yan; Ding, Qingjie; Jia, Kaicheng; Sun, Luzhao; et al.
Abstract: Formation of graphene wrinkle arrays can periodically alter the electrical properties and chemical reactivity of graphene, which is promising for numerous applications. However, large‐area fabrication of graphene wrinkle arrays remains unachievable with a high density and defined orientations, especially on rigid substrates. Herein, relying on the understanding of the formation mechanism of transfer‐related graphene wrinkles, the graphene wrinkle arrays are fabricated without altering the crystalline orientation of entire graphene films. The choice of the transfer medium that has poor wettability on the corrugated surface of graphene is proven to be the key for the formation of wrinkles. This work provides a deep understanding of formation process of transfer‐related graphene wrinkles and opens up a new way for periodically modifying the surface properties of graphene for potential applications, including direct growth of AlN epilayers and deep ultraviolet light emitting diodes. Abstract : With the assistance of the transfer medium that has poor wettability on the corrugated surface of graphene, the graphene wrinkle arrays are successfully fabricated without altering the crystalline orientation of entire graphene films, which is promising for numerous applications. This work opens up a new way for periodically modifying the surface properties of graphene for epitaxial growth of AlN films.